An improved immunoassay detects Aβ oligomers in human biofluids: their CSF levels rise with tau and phosphotau levels - Ting Yang; Yi Ran Xu; Shanxue Jin; Nagendran Ramalingam; Jean-Pierre Bellier; Alexandra M. Lish; Beth L. Ostaszewski; Tracy Young-Pearse; Lei Liu; Hyun-Sik Yang; Jasmeer P. Chhatwal; Trebor L. Lawton; et al. (Alzheimer’s Research & Therapy)
Abstract Background Diffusible Aβ oligomers (oAβ) confer cytotoxicity in Alzheimer’s disease. The dynamic complexity of this hydrophobic analyte means few immunoassays exist to quantify oAβ in CSF and plasma. Methods We characterized antibody 71A1 to a cyclized dimer of Aβ9-18 for oAβ preference over monomers by surface plasmon resonance. We improved an earlier bead-based immunoassay by using 71A1 streptavidin plates for capture and N-terminal antibody 3D6 for detection. Numerous controls systematically validated accuracy. Results 71A1 showed highly selective binding kinetics to Aβ oligomers over monomers. It enriched bioactive oligomers from AD brain that altered neuronal excitatory currents and calcium transients. 71A1/3D6 immunoassay exhibited specificity and reproducibility in human biofluids. CSF oAβ levels correlated positively with CSF tau and phosphorylated-tau-181. APP and PS1 FAD mutations increased oAβ levels in human neuronal media. Conclusions CSF oAβ levels rise in concert with rising tau levels. A new plate-based ELISA offers improved consistency, less sample volume, and lower cost, thus better suited to quantify this challenging analyte.